Entre o território vivo e letras mortas: um estudo sobre as políticas educacionais para a formação de trabalhadores em Conceição do Jacuípe, de 2006–2016 - Neres, Jocelandia Cerqueira (2022)
What is the implication of state and municipal Public Policies in the reality of professional training in Conceição de Jacuípe, in the Portal do Sertão Territory? Aiming to answer this question, this work analyzes how such Public Policies dialogue for the construction of a teaching model that meets the integral formation of the subjects considering their socio-historical, political and economic context that, in the case of Bahia, is circumscribed by the Territories of Identity. To this end, this study investigates the Educational Policies for Professional Education Integrated to High School implemented in the state of Bahia between 2006 and 2016, based on the analysis of the goals for Professional Education of the State Education Plan and the Municipal Plan of Education. Education in Conceição do Jacuípe - municipality traditionally known as “Berimbau”. This study is also carried out in the light of the territorial policy adopted by the Government of Bahia, which is mainly included in Decree 12.354/2010 and in Law 13.124/2014 and demarcates the municipalities of the Identity Territory of Portal do Sertão in which Conceição do Jacuípe is located. inserted . In the search for understanding the dynamics between Public Policies, Territories and their subjects, a qualitative approach was adopted for the research, using the Document Analysis Methodology, based on the procedures defined by Bardin's content analysis, based on the Critical Social Theory. It is concluded that Educational Policies reflect the context of the historical moment in which they were produced, and in Brazil, they have been reproducing the neoliberal character, and the Territory needs to be the first reference in the elaboration of these.